'Depending on where I am…' Hair, travelling and the performance of identity among Black and mixed‐race women. (18th October 2022) - Lukate, Johanna M.; Foster, Juliet L.
Abstract: A growing interdisciplinary literature examines the role of hair textures and styles in Black and mixed‐race women's identity performances. Through an analysis of travel narratives, this paper extends and complements research on the context‐dependency of racialized identity performances. This paper presents an analysis of 24 qualitative interviews with Black and mixed‐race women in England and Germany. The question it seeks to answer is: 'How do changes in context alter Black and mixed‐race women's hairstyling practices as a performance of identity?' Navigating a novel context could lead the women to (1) conform to local standards of beauty and femininity, (2) resist external expectations, (3) try out novel performances and (4) negotiate the complex performance of belonging. All in all, this paper shows that Black and mixed‐race women dialogically re/negotiated and performatively re/created how they identify and how they are identified by others as they moved from one context to another.